2020
DOI: 10.1097/01.asw.0000651456.30210.8a
|View full text |Cite
|
Sign up to set email alerts
|

Examining Social Risk Factors in a Pressure Ulcer Quality Measure for Three Post-Acute Care Settings

Abstract: OBJECTIVE To describe and explore relationships between social demographic factors and incidence or worsening of pressure ulcer scores among post-acute care (PAC) settings. DESIGN The authors present the incidence of new or worsening pressure ulcers stratified by self-reported patient race and sex. Investigators used logistic regression modeling to examine relative risk of developing new or worsened pressure ulcers by sociodemographic status and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 29 publications
2
20
1
Order By: Relevance
“…Regression analyses also confirmed that male gender was significantly associated with higher odds of PI. 26 Obesity seemed to offer some protection for PIs, which is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regression analyses also confirmed that male gender was significantly associated with higher odds of PI. 26 Obesity seemed to offer some protection for PIs, which is consistent with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“… 24 , 25 This study found that male gender was a risk factor for development of a PI during the acute hospital stay. 26 This variable has limited evidence in the literature to support their classification as risk factors for PIs. 29 , 30 , 31 , 32 , 33 , 34 However, these factors have been shown to play a role in the severity of COVID-19 morbidity, which may play a role in the development of PIs, and in the case of malnutrition (low blood albumin levels), and PI severity.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 13 studies for the topic of pressure injuries (PIs). Of these 13 studies, 7 studies used a retrospective cohort design, 230 231 232 233 234 235 236 3 used a prospective cohort design, 237 238 239 1 used a clinical trial, 240 1 used a cross-sectional design, 241 and 1 used secondary data analysis. 242 A variety of data sources were used for the studies, including EHR data, 233 234 238 239 data warehouses, 230 231 235 236 a publicly available dataset, 232 sensor data, 240 242 and surveys as the primary collection tool.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 13 studies, 7 studies used a retrospective cohort design, 230 231 232 233 234 235 236 3 used a prospective cohort design, 237 238 239 1 used a clinical trial, 240 1 used a cross-sectional design, 241 and 1 used secondary data analysis. 242 A variety of data sources were used for the studies, including EHR data, 233 234 238 239 data warehouses, 230 231 235 236 a publicly available dataset, 232 sensor data, 240 242 and surveys as the primary collection tool. 237 The samples across studies were adult patients admitted in hospitals, 230 231 232 234 236 238 239 adults in residential hospices, 237 elderly patients in nursing homes (NHs), 241 Medicare beneficiaries, 235 and adults (unspecified).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation